Long-Term Prospective Study of the Influence of Estrone Levels on Events in Postmenopausal Women with or at High Risk for Coronary Artery Disease - Antonio de Padua Mansur; Tereza Cristina B. F. Silva; Julio Yoshio Takada; Solange Desirée Avakian; Célia Maria C. Strunz; Luiz Antonio Machado César; José Mendes Aldrighi; José Antonio F. Ramires (The Scientific World Journal)
Background. The link between endogenous estrogen, coronary artery disease (CAD), and death in postmenopausal women is uncertain. We analyzed the association between death and blood levels of estrone in postmenopausal women with known coronary artery disease (CAD) or with a high-risk factor score for CAD. Methods. 251 postmenopausal women age 50–90 years not on estrogen therapy. Fasting blood for estrone and heart disease risk factors were collected at baseline. Women were grouped according to their estrone levels (<15 and ≥15 pg/mL). Fatal events were recorded after 5.8±1.4 years of followup. Results. The Kaplan-Meier survival curve showed a significant trend (P=0.039) of greater all-cause mortality in women with low estrone levels (<15 pg/mL). Cox multivariate regression analysis model adjusted for body mass index, diabetes, dyslipidemia, family history, and estrone showed estrone (OR=0.45; P=0.038) as the only independent variable for all-cause mortality. Multivariate regression model adjusted for age, body mass index, hypertension, diabetes, dyslipidemia, family history, and estrone showed that only age (OR=1.06; P=0.017) was an independent predictor of all-cause mortality. Conclusions. Postmenopausal women with known CAD or with a high-risk factor score for CAD and low estrone levels (<15 pg/mL) had increased all-cause mortality.